Persistence of Plasmids Targeted by Crispr Interference in Bacterial Populations - Ispolatov, y (National Academy of Sciences, 2022)
CRISPR-Cas systems provide prokaryotes with an RNA-guided defense against foreign mobile genetic elements (MGEs) such as plasmids and viruses. A common mechanism by which MGEs avoid interference by CRISPR consists of acquisition of escape mutations in regions targeted by CRISPR. Here, using microbiological, live microscopy and microfluidics analyses we demonstrate that plasmids can persist for multiple generations in some Escherichia coli cell lineages at conditions of continuous targeting by the type I-E CRISPR-Cas system. We used mathematical modeling to show how plasmid persistence in a subpopulation of cells mounting CRISPR interference is achieved due to the stochastic nature of CRISPR interference and plasmid replication events. We hypothesize that the observed complex dynamics provides bacterial populations with long-term benefits due to continuous maintenance of mobile genetic elements in some cells, which leads to diversification of phenotypes in the entire community and allows rapid changes in the population structure to meet the demands of a changing environment. © 2022 the Author(s).
Keywords: CRISPR-Cas; CRISPR interference; mobile genetic elements